Traditional Marriage of Wayah Dalem Keraton Surakarta Hadiningrat in the Perspective of Islamic Law - Suri , Karlin Permata; Yusdani (Universitas Islam Indonesia, 2022)
Marriage is something that is sacred, great, and monumental for every spouse. Marriage is not just following religion and continuing the instincts of the ancestors to form a family in a legal bond between men and women, but also has a very deep and broad meaning for human life towards the ark of life as it aspires to be. The Keraton Surakarta Hadiningrat Traditional Marriage has a unique procedure. In traditional families, the wedding ceremony is carried out according to hereditary tradition, which consists of many sub-ceremonies, namely penembung, paningset, liru kalpika, sawon ancestors, wilujengan, pasang tarub, tuwuhan, siraman, paes, sesadeyan dawet, sengkeran, mindodareni, ijab/marriage, panggih, sepasaran, and wilujengan. Javanese traditional wedding procedures with Islamic wedding procedures need to be studied more deeply, because the Javanese Muslim community can adjust the style of dress and decoration in accordance with Islamic provisions. This study uses qualitative methods to answer research questions: How is the customary marriage procession of the Keraton Surakarta Hadiningrat? What are the stages of the Keraton Surakarta Hadiningrat customary court with Islamic law? What is the meaning of the symbols of the Keraton Surakarta Hadiningrat customary procession? The results of the study show that the custom of the great marriage at the Keraton Surakarta Hadiningrat does not conflict with the provisions of Islamic law; the conditions for harmonious marriage are met; and according to the laws in force in Indonesia, it is also appropriate.